Britain and the Dictatorships of Argentina and Chile, 1973-82 Foreign Policy, Corporations and Social Movements - Livingstone, Grace (Security, Conflict and Cooperation in the Contemporary World, 2018)
This book explores the links between the British government and the dictatorships of Argentina and Chile, 1973-82, using newly-opened British archives. It gives the most complete picture to date of British arms sales, military visits and diplomatic links with the Argentine and Chilean military regimes before the Falklands war. It also provides new evidence that Britain had strategic and economic interests in the Falkland Islands and was keen to exploit the oil around the Islands. It looks at the impact of private corporations and social movements, such as the Chile Solidarity Campaign and human rights groups, on foreign policy. By analyzing the social background of British diplomats and tracing the informal social networks between government officials and the private sector, it considers the pro-business biases of state officials. It describes how the Foreign Office tried to dissuade the Labour governments of 1974-79 from imposing sanctions on the Pinochet regime in Chile and discusses whether un-elected officials place constraints on politicians aiming to pursue an 'ethical' foreign policy. .